Environmental Impact on Sustainability in The Old City of Jakarta Tourism Destinations - Prama Hardika Suyono; Rizki Nurul Nugraha (Westscience Press, 2024)
This research aims to identify and analyze the environmental impacts that may occur in the Old City of Jakarta Tourism and its impact on environmental sustainability in the area. The research methods used were field surveys, interviews, and data analysis using SWOC. Research findings show that tourist activities in the Old City of Jakarta have a significant impact on the environment, including waste management, building conservation, tourist behavior and community participation. These impacts can affect the sustainability of Jakarta's Old City tourism, and can also threaten the sustainability of Jakarta's Old City tourism if not handled quickly and appropriately. Therefore, recommendations are given to implement mitigation and sustainable management measures to minimize negative impacts and increase environmental sustainability in Jakarta's Old City Tourism.